2003
DOI: 10.1097/01.aud.0000051846.71105.af
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Changes in Children’s Speech and Voice Physiology after Cochlear Implantation

Abstract: Children who received cochlear implants after 5 yr of age and who were educated in a Total Communication setting showed persistence and further development of deviant speech/voice behaviors for several years post-cochlear implant. Although our findings cannot be generalized to other populations of children with cochlear implants (i.e., those who were implanted earlier, those educated in auditory-oral programs), it seems wisest at the present time not to assume that children's deviant speech/voice behaviors wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
1
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 41 publications
2
40
1
4
Order By: Relevance
“…Crianças que recebem o implante coclear na fase pré-lingüística (ou seja, até o 3º ano de vida), apresentam um melhor controle acústico sobre sua fala, normalizando sua freqüência fundamental e melhorando sua habilidade articulatória 21 . Contudo, comparados com crianças ouvintes da mesma idade, as crianças implantadas ainda estão longe de apresentarem as mesmas características dos parâmetros de pitch, intensidade, fluência e articulação (freqüência) 22 . Parâmetros Acústicos As medidas acústicas também são apresentadas em vários estudos, descrevendo os parâmetros acús-ticos referentes à qualidade vocal do deficiente auditivo, relacionando-os aos dados preceptivo-auditivos e fisiológicos, e permitindo a diferenciação entre articulação e produção de determinados sons.…”
Section: Resultsunclassified
“…Crianças que recebem o implante coclear na fase pré-lingüística (ou seja, até o 3º ano de vida), apresentam um melhor controle acústico sobre sua fala, normalizando sua freqüência fundamental e melhorando sua habilidade articulatória 21 . Contudo, comparados com crianças ouvintes da mesma idade, as crianças implantadas ainda estão longe de apresentarem as mesmas características dos parâmetros de pitch, intensidade, fluência e articulação (freqüência) 22 . Parâmetros Acústicos As medidas acústicas também são apresentadas em vários estudos, descrevendo os parâmetros acús-ticos referentes à qualidade vocal do deficiente auditivo, relacionando-os aos dados preceptivo-auditivos e fisiológicos, e permitindo a diferenciação entre articulação e produção de determinados sons.…”
Section: Resultsunclassified
“…Congenitally deaf speakers tend to have a higher F0 than speakers with normal hearing [6][7][8]. On the other hand, some investigators did not find a higher F0 in young hearingimpaired children than they found in the controls [9].…”
Section: Introductionmentioning
confidence: 99%
“…They usually have higher F0 than individuals with normal hearing [15][16][17]. They may demonstrate excessive pitch variation, resulting in pitch breaks and abrupt changes [17,18].…”
Section: Discussionmentioning
confidence: 99%